MODERN APPROACHES ALLOCATION AND THE LITHOSPHERE MAGNETIC FIELD MODELING - Nikitchenko, K. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This article aims to review the available and effective methods of determining the lithosphere magnetic field, problems of its extraction and interpretation. These methods will be briefly analyzed. The paper emphasizes the features of each technique, the scope of application and prospects of further development. In the recent years, a large amount of magnetic vector and scalar data have been measured or made available to scientists. They cover different ranges of altitudes from ground to satellite levels and have high horizontal densities over some geographical areas. Processing these potential field data may require alternatives to the widely used Spherical Harmonics. During the past decades, new techniques have been proposed to model regionally the magnetic measurements. They complement the set of older approaches that were revived and sometimes revised in the meantime. The amount of available techniques is intimidating and one often wonders which method is the most appropriate for what purpose. Regional modeling techniques can be divided into two groups. The first method is based on spherical splines, wavelets or other localized spherical functions. The second one includes methods based on a level approximation, such as rectangular and cylindrical harmonic analysis; methods that take into account the spherical shape of the Earth (SCHA, Revised-SCHA). Characteristics of each method and limits of their use were determined. Choice of optimal methods is based on existing data and prospects for further development of regional magnetic modeling. The problem of the separation of fields is solved at the entire stage of the development of geomagnetism, but has no unambiguous solution in connection with the ambiguity of the inverse problem of magneto-prospecting. In order to represent and further analyze the field (as a rule, its anomalous component associated with the lithosphere), the medium is approximated by a number of cells with positive or negative magnetization, the effect of which can be chosen from any type of magnetic anomaly. In spite of the fact that such an environment model is not geologic, it allows further transformation with the field (recalculations, averaging, etc.).